Sex and Population Drive Interindividual Variations in a Cognitive Task Across Three Populations of Wild Zebrafish - Daniel, Danita K.; Bhat, Anuradha (Frontiers in Psychology, 2022)
Animal personality refers to the consistency of variation in behavior among individuals which may be the driving force behind variations in complex behaviours as well. Individual personality could predict how an organism would perform in personality and cognition related tasks, as well as survive and thrive in its environment Therefore, we would expect inter-individual variations in many behaviors, which would persist even if habituation occurred. Our study uses wild-caught zebrafish (Danio rerio) from three natural habitats with differing ecological regimes, to understand how consistency and repeatability in boldness, exploration and spatial ability varies across and within populations even when habituation causes change in behavior. We found that the extent of individual variation differs between populations, with dynamic habitats showing similar repeatability. This indicates that habitat conditions not only drive the extent of individual variations, but also the factors that cause them. We also delved into what causes individual variation within populations and found that sex played an important role in some populations for some behaviors, while in others, the variation was caused by other unknown factors. This study underlines the importance of studying inter-individual differences as the phenomenon that underpins multiple behavioral traits and explains the possible role of environmental and inherent factors that drive these differences.